A review of methods for assessing and managing market access and biosecurity risks using systems approaches - Jamieson, L.E.; DeSilva, H.N.; Worner, S.P.; Rogers, D.J.; Hill, M.G.; Walker, J.T.S. (New Zealand Plant Protection, 2013)
Systems approaches to managing risks on a pathway are increasingly seen as alternatives to singlepoint risk management treatments applied at the border One key challenge of systems approaches is the difficulty in measuring risk management effectiveness across an entire pathway comprising many complex processes The World Trade Organisation (WTO) agreement on the application of Sanitary and Phytosanitary measures (SPS) states that measures must be applied only to the extent required to achieve an appropriate degree of sanitary/phytosanitary protection (not unnecessarily traderestrictive) and must use sciencebased risk assessment The framework for import risk analysis within the scope of the International Plant Protection Convention (IPPC) is outlined in the International Standards for Phytosanitary Measures (ISPMs) Although a systems approach and independent risk reduction system processes are described in various ISPMs the methodology for determining risk across an entire pathway with complex processes is not This contribution reviews methodologies with potential for such use